The mirrored cationic peptide as miRNA vehicle for efficient lung cancer therapy - Wenyan Xu; Lingran Du; Lina Yu; Huiyu Cen; Fangyu Lin; Siran Wang; Zhixiong Ruan; Zhongxiao Lin; Xin Zhang; Na Zhou; Jishuo Chang; Xiyong Yu; et al. (MedComm, 2023)
Abstract Gene therapy has emerged as a potential approach for lung cancer therapy. However, the application of gene therapy is still limited by their properties, such as low specificity to the cancer cells, negatively charged groups, short systemic circulation time, and rapid degradation by nucleases. The progression of lung adenocarcinoma (LUAD) can be promoted through the methylation process of miR‐148a‐3p promoter, as confirmed by our previous research. In the current study, we are the first to design a mirrored Arg‐Gly‐Asp (RGD)‐modified cationic peptide (RD24) as a microRNA (miRNA) vehicle, which enabled to pack the miRNA (miR‐148a‐3p) efficiently and generate RD24/miR‐148a‐3p nanoparticles (RPRIN) by self‐assembling. RPRIN exhibited a high transfection efficiency in lung cancer cells via the conjugation between RGD and integrins on the surface of lung cancer cells. Furthermore, RD24 showed matrix metallopeptidase 2 (MMP2) responsiveness, which improved lung cancer cell inhibition induced by the miRNA intracellularly. In addition, RPRIN exhibits several advantages, such as prolonged circulation duration, reduced toxicity, and immune escape. Experiments conducted both in vitro and in vivo revealed that RPRIN effectively suppressed the growth and progression of lung cancer. Thus, the mirrored RGD‐modified cationic peptide showed great potential in transducing miRNA for lung cancer therapy.